On the best possible description of an exceptional set in asymptotic estimates for Laplace–Stieltjes integrals - O. B. Skaskiv; D. Yu. Zikrach (Математичні Студії, 2011)
For the Laplace–Stieltjes integrals new description of the exceptional set in asymptotic upper estimates in terms of the maximum of the integrand function is obtained.